Competitiveness of the Polish Dairy Industry in the EU Market - Szczubełek, Grzegorz (Olsztyn Economic Journal, 2019)
The structural transformations occurring in the Polish dairy industry, to a large extent, arise from the processes of its adaptation to the uniform EU market conditions. The thorough mod-ernization of milk production and processing technologies has enabled the producers to achieve a considerable improvement of the quality of dairy products, which alongside the cost and price advantage of Polish dairy producers is an important contributor to the competitiveness in the EU market. The purpose of this study has been to make an assessment of the prospects for further growth in the competitiveness of the Polish dairy industry in international markets. The dairy industry in Poland was compared to selected EU countries with regards to the quality of raw ma-terial supplies, the worth and structure of the production of dairy products, labour efficiency, and production concentration. The study showed that any further growth in the export of Polish dairy products will require more intensive promotional campaigns, so that European consumers would be able to identify Poland with a greater array of dairy products.